Islamic Social Entrepreneurship Model Of Business Women In Pandemic Era: Evidence From Indonesia - Nurul Asfiah; Ratya Shafira Arifiani; Rizki Febriani; Yeyen Pratika (Universitas Muhammadiyah Malang, 2022)
The pandemic has caused the economic sector to change, especially for businesses in the social sector. This study aims to create a business model with the concept of Islamic Social Entrepreneurship for entrepreneurial women in the pandemic Covid-19 era. This study is based on the case of Micro and Small Enterprises (SMEs) belonging to the